2021
DOI: 10.1161/hypertensionaha.120.15336
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pulse Wave Velocity Predicts Cardiovascular Events and Mortality in Patients Undergoing Coronary Angiography

Abstract: Aortic pulse wave velocity (PWV) is directly related to arterial stiffness. Different methods for the determination of PWV coexist. The aim of this prospective study was to evaluate the prognostic value of PWV in high-risk patients with suspected coronary artery disease undergoing invasive angiography and to compare 3 different methods for assessing PWV. In 1040 patients, invasive PWV (iPWV) was measured during catheter pullback. Additionally, PWV was estimated with a model incorporating age, central systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 65 publications
4
59
0
3
Order By: Relevance
“…An individual participant meta-analysis (16 studies, 17,635 subjects) confirmed a similar predictive value of carotid-femoral PWV in women and men [107]. A recent study suggests that invasive PWV, estimated PWV (a model incorporating age, central systolic blood pressure, and pulse waveform characteristics obtained from noninvasive measurements) and formula-based PWV (based on age and blood pressure) were independent predictors of CV events and mortality in women and men, but higher hazard ratios were found in women [108]. The picture is less clear for other vascular ageing measures: a recent meta-analysis on the predictive value of brachial-ankle PWV did not report sex-disaggregated data [109]; in a recent meta-analysis investigating the predictive value of intima-media thickness (IMT) progression in clinical trials results are not significantly influenced by the proportion of women included in the study [110]; in another meta-analysis, the association between FMD and cardiovascular outcomes was stronger in studies recruiting .50% men than in those recruiting ,50% men [111].…”
Section: Sex and Gender Differences In The Prognostic Relevance Of Arterial Stiffnessmentioning
confidence: 72%
“…An individual participant meta-analysis (16 studies, 17,635 subjects) confirmed a similar predictive value of carotid-femoral PWV in women and men [107]. A recent study suggests that invasive PWV, estimated PWV (a model incorporating age, central systolic blood pressure, and pulse waveform characteristics obtained from noninvasive measurements) and formula-based PWV (based on age and blood pressure) were independent predictors of CV events and mortality in women and men, but higher hazard ratios were found in women [108]. The picture is less clear for other vascular ageing measures: a recent meta-analysis on the predictive value of brachial-ankle PWV did not report sex-disaggregated data [109]; in a recent meta-analysis investigating the predictive value of intima-media thickness (IMT) progression in clinical trials results are not significantly influenced by the proportion of women included in the study [110]; in another meta-analysis, the association between FMD and cardiovascular outcomes was stronger in studies recruiting .50% men than in those recruiting ,50% men [111].…”
Section: Sex and Gender Differences In The Prognostic Relevance Of Arterial Stiffnessmentioning
confidence: 72%
“…Our results suggest, however, that validity of both devices (Mobil-O-Graph algorithm and SphygmoCor XCEL) may require further investigation in African populations, particularly to determine if stunting and earlier vascular ageing impact the accuracy of results. In addition, recent research by Hametner et al [ 61 ] has shown that both invasive and noninvasive measurements of PWV are not only suitable measures of arterial stiffness but also are predictors of cardiovascular events and mortality. Therefore, further research is needed to confirm the accuracy and potential predictability of these PWV measures by the Mobil-O-Graph and SphygmoCor XCEL in the South African population, including children, women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos anos, várias evidências têm demonstrado forte e independente associação dos marcadores de EVA descritos acima e eventos cardiovasculares e aterosclerose, destacando-se as medidas de rigidez arterial 20,21,22,23,24,25,26 e espessura intima-medial 17 de carótida como bons preditores de risco cardiovascular.…”
Section: Marcadores De Envelhecimento Vascular Precoce E Associação Com Risco Cardiovascular E Ateroscleroseunclassified
“…No que se refere à presença ou significância de DAC, não observamos diferença estatisticamente significativa dos valores de VOP entre os grupos, embora nos pacientes com DAC significativa pela estimativa visual, os valores de VOP tenderam a ser maiores do que aqueles sem lesão grave (p=0.05). Poderiamos argumentar que se o número de indivíduos fosse maior, estas diferenças poderiam atingir a significância estatística estimada, como alguns estudos demonstraram incluindo maior número de individuos 25 .…”
Section: Medida Da Velocidade De Onda De Pulsounclassified
See 1 more Smart Citation